Pengaruh Subtitusi Tepung Daun Kelor (Moringa Oleifera) terhadap Kadar Zat Besi dan Vitamin C Crackers - Devina Kemala Pratidina; Sudrajah Warajati Kisnawaty; Pramudya Kurnia (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
An increase up to 50% in blood volume during pregnancy leads to a heightened demand for vitamin C and iron, which are essential for supporting erythrocyte formation and facilitating iron absorption. One plant rich in vitamins A, B, C, and bioavailable iron is Moringa leaves. Moringa leaf flour can be utilized as a substitute ingredient in various food products, including crackers. This study was conducted to examine the effect of substituting Moringa oleifera leaf flour on the iron and vitamin C content of cracker products. An experimental research design was employed using a Completely Randomized Design (CRD) with four substitution levels. Analytical methods were carried out using ICP-OES and HPLC for iron and vitamin C content. The Kruskal-Wallis test and the Mann-Whitney test were utilized to analyze the data obtained from the study. The results indicate that the incorporation of Moringa leaf flour has a significant effect on the iron and vitamin C content of crackers (p ≤ 0.05). Iron content increased at 10% and 15% substitution levels, then decreased at 20% substitution. Vitamin C content decreased as moringa leaf flour substitution increased, from 0.44 mg at 0% substitution to 0.16 mg at 20% substitution. The decrease in vitamin C content was due to high-temperature baking, which caused damage, and exposure to oxygen during molding, triggering oxidation. The iron and vitamin C content in the cracker products was significantly influenced by the substitution of moringa leaf flour.